Barriers and facilitators to smoking cessation in pregnancy and in the post‐partum period: The health care professionals' perspective. Issue 3 (15th May 2018) - Naughton, Felix; Hopewell, Sarah; Sinclair, Lesley; McCaughan, Dorothy; McKell, Jennifer; Bauld, Linda
Abstract : Objectives: Health care professionals and the health care environment play a central role in protecting pregnant and post‐partum women and their infants from smoking‐related harms. This study aimed to better understand the health professional's perspective on how interactions between women, health care professionals, and the environment influence how smoking is managed. Design: Semi‐structured interviews and focus groups. Methods: Data were from 48 health care staff involved in antenatal or post‐partum care at two UK sites, including midwives, obstetricians, health visitors, GPs, pharmacists, service commissioners, and Stop Smoking Service (SSS) advisors and managers. Thematic analysis was guided by a social–ecological framework (SEF). Results: Themes were divided across three SEF levels and represented factors connected to the management of smoking in the health care context and the beliefs and behaviour of pregnant or post‐partum smokers. Organizational level: Service reconfigurations, 'last resort' nicotine replacement therapy prescribing policies, and non‐mandatory training were largely negative factors. There were mixed views on opt‐out referral pathways and positive views on carbon monoxide monitoring. Interpersonal level: Protection of client–professional relationships often inhibited frank discussions about smoking, and weak interservice relationships affected SSS referral motivation and quality. Individual level: Professionals felt community midwives had primary responsibility for managing smoking, although midwives felt underskilled doing this. Midwives' perceived priority for addressing smoking was influenced by the demands from unrelated organizational initiatives. Conclusions: Opportunities to improve clinical support for pregnant smokers exist at organizational, interservice, and health care professional levels. Interactions between levels reflect the importance of simultaneously addressing different level‐specific barriers to smoking cessation in pregnancy. Statement of contribution What is already known on this subject? Few health care professionals discuss smoking cessation support with pregnant or post‐partum women. Identified health care professional‐related barriers to supporting pregnant and post‐partum women to stop smoking include deficits in knowledge and confidence, perceived lack of time, and concerns about damaging client relationships. There is currently a gap in understanding regarding the barriers and facilitators to supporting this group and how interactions between the health care environment and health care professionals influence the way smoking is addressed. What does this study add? This study identifies modifiable factors that can influence cessation support delivery to pregnant and post‐partum women. These factors are mapped across organizational, interpersonal, and individual health care professional levels. Service structure, communication pathways, and policies appear to influence what cessation support is offered. Interpersonal and individual factors influence how this support is delivered.